Can artificial ecological corridors be used for ecological restoration of cultivated land in Chinese Mollisols? - Xu, HuiBo; Wu, SongTao; Diehl, Jessica Ann (Frontiers in Plant Science, 2022)
Artificial ecological corridors (AECs) are internationally recognized as a standard method for restoring the regional ecological environment. However, the coupling relationship between AECs and soil quality has rarely been studied. Harbin, a typical mollisols region in the cold area of China, has severe soil problems, and remediation is urgently needed. We quantitatively evaluated the construction factors of ecological corridors to predict the long-term impact of AECs already built along Harbin’s Ashi River on soil eco-chemical indices. We studied the ecological restoration of secondary woodland, cultivated land within the ecological corridor, and cultivated land outside the influence range of the corridor under the influence of continuous recovery time and different locations in the corridor. Soil samples were taken from 5 plots, with a total of 161 samples, and we monitored 12 indices of soil ecological characteristics. Results: 1. We believe that the quality restoration of mollisols through ecological corridors has great application potential. Based on the low-cost natural restoration of ecological corridors, the highest values of TP and SOM in soil indices were detected in corridors (restored for more than 10 years). In addition, after ten years of recovery, pH and EC in the ecological corridor returned to normal from high levels in cultivated land that far exceeded the reference values. 2. The recovery process of mollisols mass begins to decrease, then increases, and finally reaches and exceeds the reference value of standard mollisols.3. Through redundancy analysis of soil samples, distance was found to be a key factor affecting soil TN, SOM, and CEC. Recovery time is crucial for soil SOC, pH, and EC. According to the TN, SOM, and CEC indices of mollisols, we recommend a unilateral width of 125-150 m. According to the SOC, pH, and EC indices of mollisols, we recommend that the AECs should complete a natural recovery cycle of a minimum of 13 years. This study reveals the change mechanism of soil quality in mollisols area corridors based on recovery time and location. We offer ideas and a scientific basis for worldwide governments in mollisols to formulate mollisol restoration policies.